2018
DOI: 10.1111/ases.12654
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term and midterm outcomes of single‐incision laparoscopic surgery for right‐sided colon cancer

Abstract: Introduction: The purpose of this study was to clarify the usefulness of SILS for right-sided colon cancer by evaluating the short-term and midterm outcomes.Methods: Between 2012 and 2017, 65 selected patients with right-sided colon cancer underwent ileocecal resection, right hemicolectomy, or transverse colectomy; all were enrolled in the study. The same well-trained surgeon performed each procedure by using a multi-instrument access port with three channels, which was placed at the umbilicus via an approxima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…There are several reports that SILC is as feasible and safe as multiple-incision laparoscopic colectomy (MLC) in colon cancer. 7 Furthermore, Suzuki et al 8 reported that the median length of the hospital stay for the SILC patients was significantly shorter compared with the MLC patients (the bowel function recovery was estimated and included in the discharge criteria).We think that SILC was less invasive than MLC, and SILC is effective and valuable for this patient. In this case, the progression of RP could be prevented by SILC.…”
Section: Discussionmentioning
confidence: 97%
“…There are several reports that SILC is as feasible and safe as multiple-incision laparoscopic colectomy (MLC) in colon cancer. 7 Furthermore, Suzuki et al 8 reported that the median length of the hospital stay for the SILC patients was significantly shorter compared with the MLC patients (the bowel function recovery was estimated and included in the discharge criteria).We think that SILC was less invasive than MLC, and SILC is effective and valuable for this patient. In this case, the progression of RP could be prevented by SILC.…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies have reported unexpected open conversion in SILS surgery, ranging from 1.4% to 9.5% 9,20,30,31 and insertion of an additional port ranging from 6.3% to 27.8%. 18,32,33 Conversion to open surgery is reported to increase postoperative complications, which results in longer hospital stays. 34 No patient in the present study experienced conversion to open surgery and none required the insertion of an additional port.…”
Section: Discussionmentioning
confidence: 99%
“…The indications for SPLC have expanded as evidence has grown regarding its short‐term oncological safety and advantages, including good cosmesis, reduced postoperative pain, and shortened hospital stay . The application of SPLC in elderly patients remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…The indications for SPLC have expanded as evidence has grown regarding its short-term oncological safety and advantages, including good cosmesis, reduced postoperative pain, and shortened hospital stay. [7][8][9][10] The application of SPLC in elderly patients remains controversial. To our knowledge, only two studies to date, both published in 2018, have specifically evaluated the outcomes of SPLC in elderly patients with colon cancer.…”
Section: Discussionmentioning
confidence: 99%